The Effectiveness of E-Module STEM Biotechnology to Empower Metacognitive Skills and Science Process Skills of High School Students with Low Academic Ability in Industrial Agriculture Areas - Bea Hana Siswati; Jekti Prihatin; Duran Corebima Aloysius (Postgraduate, University of Mataram, 2024)
Metacognitive skills are vital for empowering students, especially in subjects like biology that are intertwined with scientific activities. Science process skills are crucial for enhancing the learning process in science. This study aimed to assess the impact of STEM e-modules in Biotechnology on metacognitive and science process skills among students in the industrial agricultural sector, particularly those with low academic proficiency. The research followed a quasi-experimental, non-equivalent control group design with a pretest-posttest research structure. The study population comprised public high schools in Jember, with class XII students from SMAN 1 Jember selected as the sample through cluster random sampling and class equivalence testing using ANOVA. Data collection involved essay tests, and prerequisite tests ensured homogeneity and normality. Hypothesis testing employed a two-way ANCOVA at a 0.5% significance level. The findings revealed that significant differences in metacognitive and science process skills when STEM e-modules were used in Biotechnology material, variations in metacognitive and science process skills based on students' academic abilities, and an interaction between STEM e-modules and academic ability on metacognitive and science process skills. This research suggests exploring the effects of STEM Biotechnology e-modules and academic ability on other dependent variables.